2020
DOI: 10.1002/ajim.23158
|View full text |Cite
|
Sign up to set email alerts
|

Prescription opioid use and associated factors among US construction workers

Abstract: Background Construction workers are among the segments of the US population that were hit hardest by the opioid prescription and overdose deaths in the past decades. Factors that underlie opioid use in construction workers have been compartmentalized and isolated in existing studies of opioid use and opioid overdose, but they ignore the overall context of their use. This study examines prescription opioid use and its association with a variety of occupational and nonoccupational factors in construction workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
0
18
1
Order By: Relevance
“…1 Journalists and researchers have documented that these tragedies are a particular concern for the construction industry. [2][3][4][5] Construction workers have the highest rate of opioid overdose deaths of all occupations. 2 While research to understand the pathways underlying these statistics has been limited, several contributing factors have been suggested, including high injury rates, workrelated musculoskeletal pain, provider prescribing behavior, drug testing, work schedules, cycles of unemployment, lack of access to treatment, work-related stress, and background drug use.…”
Section: Introductionmentioning
confidence: 99%
“…1 Journalists and researchers have documented that these tragedies are a particular concern for the construction industry. [2][3][4][5] Construction workers have the highest rate of opioid overdose deaths of all occupations. 2 While research to understand the pathways underlying these statistics has been limited, several contributing factors have been suggested, including high injury rates, workrelated musculoskeletal pain, provider prescribing behavior, drug testing, work schedules, cycles of unemployment, lack of access to treatment, work-related stress, and background drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that occupational injuries are a likely risk factor for drug overdose deaths 4,9,12–18 . In Massachusetts, among the four occupations with significant increases in drug overdose deaths, two (healthcare support and building and grounds cleaning) had increases in the rate of occupational injuries and illnesses in 2020 compared with previous years 52 .…”
Section: Discussionmentioning
confidence: 97%
“…51 Previous research has demonstrated that occupational injuries are a likely risk factor for drug overdose deaths. 4,9,[12][13][14][15][16][17][18] In Massachusetts, among the four occupations with significant increases in drug overdose deaths, two (healthcare support and building and grounds cleaning) had increases in the rate of occupational injuries and illnesses in 2020 compared with previous years. 52 It should be noted that some of these increases may be driven by increases in occupational illnesses (primarily COVID-19), which contributed to increases in occupational injuries and illnesses rates in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the average annual prevalence of OUD in this sample of 0.8% is likely underestimated since only workers who seek medical treatment could receive a diagnosis and some workers may seek treatment for health conditions unrelated to OUD so fail to receive a diagnosis for OUD 47 . Past studies suggest that other reasons for the underestimation of OUD diagnosis among construction workers is due to failure to seek treatment from lack of health insurance, 48 suffering from mental distress so avoid seeking treatment, 49 and low job security so fear of taking time off work 50‐52 . Despite this limitation, health claims provide a means to show associations between prescription opioids and development of OUD among those workers who seek treatment.…”
Section: Discussionmentioning
confidence: 99%